Zaman akhir dan akhir zaman: tantangan diskursus dalam pemenuhan kesempurnaan eskatologi - Mau, Marthen; Hia, Septinus; Amid, Markus (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2023)
Some of God's people find it difficult to distinguish between the terms the last days and the end of time, therefore an accurate explanation is needed for His people to understand the two terms well. The end times are past and present times that are focused on the event of Jesus' presence into the world for the first time through His birth. Therefore, the first coming of Jesus to the world signifies the end times have begun. Meanwhile, the end of time is a reference marked by the last presence of Jesus to bring separation between the righteous and the wicked, so that the wicked can be punished according to their deeds. This study aims to describe the end times and the end times a discourse challenge in fulfilling the perfection of eschatology. So, to produce good writing, the writer uses a qualitative research method with a literature approach. This research results in the full fulfillment of eschatology being at the second coming of Christ in the last days.